Analysis of Alternatives for Providing Icebreaking Services in Estonia: Final Report - Tapaninen Ulla; Palu Riina; Kujala Pentti; Uiboupin Rivo; Rikka Sander; Maljutenko Ilja; Hunt Tõnis; Musharraf Mashrura; Kondratenko Aleksandr; Lu Liangliang; Mylly Markku; Ojala Lauri; et al. (Tallinn University of Technology (TalTech), 2025)
The development of powerful icebreakers and ice-strengthened cargo vessels has made winter navigation possible in the northern parts of the Baltic Sea as well as in some other seasonally, or even permanently, ice-covered sea areas. Thus the ice barriers, which previously closed these coasts and sea areas from shipping, have been mostly overcome.
Briefly, the consequences of the current hazards of winter navigation seem to be limited to minor structural damage. No ice related ship disasters with large-scale consequences measurable in human or environmental losses have taken place in the Baltic Sea during the last decades. However, it should not be forgotten that some of the worst accidents in the history of shipping are closely related to ice. Titanic hit an iceberg in 1912 with the loss of life over 1500 persons. Exxon Valdez was grounded in 1989 when trying to avoid ice on its route with the result of more than 40 000 tons of spilled oil. This kind of huge disasters must be avoided in the Baltic Sea by careful risk management. On the other hand, the ability to counteract small but frequently occurring accidents, oil spills for instance, is important, too.
The amount and patterns of traffic in the Baltic Sea have been in a process of a rapid and remarkable change after 1990. The ship traffic in the Gulf of Finland has grown considerably during the last decades, and it is still growing, which is a result of growing economic activity in the area. Covid-19, war in Ukraine and related sanctions have had a decreasing effect on the traffic, but recovery is expected.
The objective of the current study is to analyse alternatives and propose an optimal solution for icebreaking services in Estonia for the period of 2029-2054, incl. which vessels or combinations of vessels the state should prefer to ensure an optimal solution that is technically and economically feasible. Also, ownership of any potential new icebreakers is to be analysed.
The analysis takes into account the traffic flows of Estonian ports receiving icebreaking services, assess the impacts of the different scenarios proposed (incl. the expediency of providing icebreaking services to ports) on the private sector and the state, highlight the investments needed for and the expected lifetime of existing icebreakers, assess the cost of different forms of ownership of the icebreakers, IMO and EU regulations, propose the optimal solutions and recommended actions for the future for the Estonian Transport Administration and other parties involved (e.g. Ministry of Climate).
The objective of organising icebreaking services in Estonia is to make sure the service and the ports using it are economically sustainable and to do so in a manner that is optimal for the economy of the entire state.